Chronic eosinophilic pneumonia with persistent decreased diffusing capacity for carbon monoxide. (15th February 2013) - Blanc, Sibylle; Albertini, Marc; Leroy, Sylvie; Giovannini-Chami, Lisa
Abstract : We report a 15-year-old girl presenting with dry cough, exertional dyspnoea, weight loss, fever and night sweats for over 1 month. Blood tests revealed hypereosinophilia, high IgE and antinuclear antibodies levels. Chest x-rays showed bilateral peripheral infiltrates mostly in the right upper lobe which was confirmed by a chest CT. Bronchoalveolar lavage showed hypercellularity with 28% of eosinophils. Idiopathic chronic eosinophilic pneumonia was confirmed after exclusion of other causes of eosinophilic pneumonia and systemic disease. The patient responded dramatically to oral corticosteroids. Oral corticotherapy was stopped after 4 months. At 8 months of follow-up, diffusing capacity for carbon monoxide (DLCO) remained moderately low (58%) with persistent mild exertional dyspnoea. Cardiopulmonary exercise testing showed muscular peripheral limitation. Even if in our patient, mild exertional dyspnoea can be partly correlated to peripheral deconditioning, DLCO should be systematically evaluated to determine follow-up studies standards, to correlate with subclinical disease, relapse risk and to codify therapeutic options.